Comparison between caudal epidural block and popliteal nerve block for postoperative analgesia in children undergoing foot surgery: a randomized controlled trial - Bumer, Tailang; Kashyap, Lokesh; Arora, M. K.; Batra, R. K.; Prasad, Ganga; Mohan, V. K.; Khan, Shah Alam (International Journal of Research in Medical Sciences, 2020)
Background: Pain following surgery in children cause discomfort, restlessness and agitation in the postoperative period which may result in an increased incidence of nausea, vomiting and maladaptive behavioural changes. Regional anaesthesia is commonly used as an adjunct to general anaesthesia for perioperative analgesia in children as part of a multimodal approach of pain relief. This study is to compare between caudal epidural block and popliteal nerve block for postoperative analgesia in children undergoing foot surgery. Methods: A prospective randomized single blind study was carried out on 30 children aged 1-12 years of either sex undergoing foot surgery. Patients were randomly assigned into caudal epidural block group and Popliteal nerve block group, 15 children each. Both groups receive 1 ml/kg of 0.25% bupivacaine. Foot surgery was carried out under general anesthesia along with regional block for all children. After completion of surgery, children were shifted to PACU and HR, BP, SPO2 were monitored. Patient was discharged from PACU after CHEOPS (1-5 years) or VAS (6-12 years) <4. Parental satisfaction, sedation score, PONV, and any other side effects were recorded. Results: Demographic data and baseline vital signs were comparable between two groups. Statistically significant difference (p=0.025) in number of attempts in giving block in group A (1.20±0.41) than group B (1.80±0.86). The mean postoperative pain scores, CHEOPS and VAS were comparable in both groups. Conclusions: Both caudal epidural block and popliteal nerve block provides comparable and adequate analgesia in children undergoing elective foot surgery.